The limitation of freedom of expression by online media in Malaysia: Analysis of legal precedents - Sahak, Suzarika; Rajamanickam, Ramalinggam; Hassan, Muhamad Sayuti (Edelweiss Applied Science and Technology, 2025)
Media freedom is a cornerstone of democratic societies, yet it is often shaped by legal precedents and regulatory frameworks. This article examines the relationship between Malaysian laws and online media freedom of expression, based on the 2021 landmark decision in the Malaysiakini case. The objective of this article is to explore the indistinct line between immunity and liability of internet intermediaries that assume the role of content publishers and to scrutinize how legal frameworks and judicial interpretations shape the landscape of online media freedom in Malaysia. This article also examines statutory provisions such as the Communications and Multimedia Act 1998, the Communications and Multimedia Content Code, and the newly enacted Online Safety Act 2025. In addition, the study offers a comparative analysis with European Court of Human Rights rulings, as well as insights from the United Kingdom and India on intermediaries. The analysis demonstrates that the Malaysiakini ruling expanded the scope of liability for online platforms by applying Section 114A of the Evidence Act 1950, raising the standard of editorial responsibility. While the decision partly aligns with international approaches, gaps remain in providing coherent protections for media freedom. This article proposes that clear guidelines should be developed to find appropriate measures to protect and balance internet freedom and online media’s freedom of expression.